High-accuracy spinal alignment monitoring using the head angle and visual distance in computer users. - Ko Hashimoto; Yusuke Sekiguchi; Kaho Matsuda; Masataka Hori; Yutaka Mizuno; Ryosuke Shibuya; Kohei Takahashi; Takahiro Onoki; Kenichiro Yahata; Shin-Ichi Izumi; Toshimi Aizawa (PLoS ONE, 2025)
Study design A Prospective Validation Study. Objectives To validate a novel, noninvasive method for estimating the spinal sagittal alignment during seated computer work, using the head angle (HA) and visual distance (VD) as primary parameters. Methods A 3D motion analysis system measured HA and VD in 21 healthy volunteers. The relationship between these parameters and spinal sagittal alignment, as determined by body surface markers, was investigated. To validate this method, radiographic measurements were taken in a separate group of 32 patients to confirm the link between body surface landmarks and actual spinal alignment. Additional variables, including gender, age, height, and weight, were incorporated into the model to improve accuracy. Results HA and VD showed significant correlations with spinal sagittal alignment, particularly for the cervical spine (C2-C7). Incorporating demographic factors further enhanced the predictive accuracy. Radiological validation confirmed that body surface marker-based measurements are closely aligned with standard radiographic indices widely used in spine surgery. Conclusions This study introduces a reliable and practical method for continuously monitoring spinal sagittal alignment in seated computer users. The approach demonstrates high accuracy, particularly for the cervical spine and holds promise for the development of posture-monitoring technologies to help prevent neck and back pain associated with prolonged computer use.